The Influence of Work Stress and Self-Efficacy on Organizational Commitment of Civil Servant Teachers (PNS) at Madrasah Tsanawiyah Negeri 1 Pontianak - Supandi, Aria; Mahdi, Irfan (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study examines the factors that affect the organizational commitment of civil servant teachers (PNS) at Madrasah Tsanawiyah Negeri 1 Pontianak. Efficient management of work-related stress and the enhancement of teachers' self-efficacy is crucial for boosting their dedication to the educational institution. Although PNS teachers exhibit a moderate level of commitment, there remains an opportunity for greater engagement in organizational activities. By implementing effective stress management and self-improvement programs, educational institutions can reinforce teachers' alignment with organizational objectives, improve their contributions, and positively influence the advancement of education in Indonesia.